2012
DOI: 10.1016/j.oraloncology.2011.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Psychological functioning of caregivers for head and neck cancer patients

Abstract: SUMMARY Patients with head and neck squamous cell carcinoma (HNSCC) often require assistance from family caregivers during the treatment and post-treatment period. This review article sought to summarize current findings regarding the psychological health of HNSCC caregivers, including factors that may be associated with poorer psychological health. Online databases (PUBMED, MEDLINE and PSYCINFO) were searched for papers published in English through September 2010 reporting on the psychological health of careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
132
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(148 citation statements)
references
References 51 publications
(88 reference statements)
11
132
3
Order By: Relevance
“…In this study and in previous studies (Hodges et al, 2005;Longacre et al, 2012;Ross et al, 2010;Verdonck-de Leeuw et al, 2007;Zwahlen et al, 2008), psychological distresses such as anxiety, fear, and disrupted daily life have been shown to affect the patients and the relatives negatively during the cancer disease progression. Relatives and patients of this study were shocked and disappointed in how the cancer diagnosis was delivered.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In this study and in previous studies (Hodges et al, 2005;Longacre et al, 2012;Ross et al, 2010;Verdonck-de Leeuw et al, 2007;Zwahlen et al, 2008), psychological distresses such as anxiety, fear, and disrupted daily life have been shown to affect the patients and the relatives negatively during the cancer disease progression. Relatives and patients of this study were shocked and disappointed in how the cancer diagnosis was delivered.…”
Section: Discussionsupporting
confidence: 63%
“…This role was challenging and could involve an overwhelming situation that could make it difficult for relatives to organize and maintain their social, emotional, and working lives. When a family member suffers from a life-threatening illness, it is common that the closest patients ignore their own health (Longacre et al, 2012;Ziegert et al, 2006). In our study, health threats in the form of sleeping difficulties and impaired eating habits in relatives were found.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Relatives described a gloomy situation, referring to psychological stress, lack of transparency and participation in health care and lack of personal support and care from care providers. Just as among the relatives in our study, other studies have also reported mental health issues among relatives of patients with HNC [78,167]. Furthermore, relatives perceived that the patients with HNC had severe physical pain, which is consistent with prior studies in which relatives often felt that the pain was worse than was self-reported by patients [168,169].…”
Section: Relatives' Experiencessupporting
confidence: 90%
“…Patients with HNC require extensive care and support and it can be difficult for relatives to fully meet this need [77]. An overview article of eleven observational studies showed that relatives often experience anxiety and depression when a patient (family member) suffers from HNC [78]. In addition, it has been reported that relatives may have to deal with an increased burden including lack of support from the family, financial problems and worsened QoL when a family member undergoes RT [79] and suffers from pain [80].…”
Section: Relatives Of Patients With Hncmentioning
confidence: 99%